Variação geográfica do tamanho e forma do crânio de mamíferos com ampla distribuição na América do Sul (Marsupialia, Xenarthra e Glires) - Magnus, Luíza Zuchetto (2018)
Skulls are complex morphological structures that exhibit phenotypic plasticity and adaptations to different functions and processes, and are under different pressures, such as the geographical or environmental ones. South America is a latitudinal broad continent, encompassing a variety of biomes and climatic conditions, revealing ecomorphological variations in many mammal species. The main objective of this study was to investigate ecogeographical patterns and determinant factors related to cranial variations in species and genera of mammals with wide geographic distribution in South America (Marsupialia, Xenarthra and Glires), based on size and shape data. From skull photographs of 1.017 specimens in the ventral view in scientific collections, geometric morphometric techniques were used to understand skull variation within the different groups. Two species of marsupials were studied in Chapter I, Caluromys philander and C. lanatus, which were similar in shape, showing similar phenotypic trajectories. The effect of size on shape (allometry) was important for C. lanatus, helping biomechanically in environments southern Amazonia. In addition, the two species were spatially structured, also showing great environmental influence (especially temperature), following the inverse of the Bergmann’s rule. In Chapter II, three species of the Xenarthra superorder (Bradypus variegatus, Tamandua tetradactyla, and Dasypus novemcinctus) presented a weak allometric influence. However, geographical (neutral) factors influenced the shape of B. variegatus and the size of T. tetradactyla, which could be a reflection of the low mobility and dispersion capacity of both species. Importantly, the environmental influence (niche) affected the three species, most notably B. variegatus (which follows the Bergmann’s rule), and D. novemcinctus (highly mobile species, being locally affected by the environment). Chapter III deals with the taxa Cuniculus paca, Hydrochoerus hydrochaeris, Nectomys spp., and Sylvilagus brasiliensis. Allometry was present notably for the genus Nectomys, suggesting an association with the sexual dimorphism found only in this genus. The environmental influence was noticeable for highly dispersive and large body size species, such as H. hydrochaeris and C. paca. These two species were also affected by spatial filters (geography), but to a lesser extent, as occurred for the other two taxa. Finally, Chapter IV addressed more specifically the masticatory apparatus (molar series and zygomatic arch) of the species of Rhipidomys and Nectomys genus. The interspecific distinction within each genus was visible for some species of Rhipidomys (size and shape), whereas the species of Nectomys presented weak disparity. In relation to the biogeographical hypotheses, the phenotypic response of each genus was divergent, with Rhipidomys shape being related to the primary productivity, and the Nectomys size related mainly to precipitation and temperature. These distinct results suggest different responses according to constraints and ecological attributes of each genus (specialist and generalist, respectively). In general, the results found in this study suggest that the response of each taxon to the various influences suffered is not necessarily the same, but depends on its characteristics and particularities that induce different cranial modifications.